FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT ACEH DALAM MEMILIH PRODUK PERBANKAN SYARIAH (Studi Kasus pada PT. Bank Aceh Cabang Banda Aceh) - Alfian, Alfian; Yahya, Faisal (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2020)
This study aims to determine the factors that influence Acehnese’s behavior in choosing Islamic banking products. In this study the author used descriptive statistical approach with quantitative research method.The primary data were collected by distributing questionnaires to 100customers of Bank Aceh Branch Banda Aceh. In choosing the samples the author used incidental sampling method, which is a sampling technique based on coincidenc, in this technique anyone can be a sample of the study as long as he/she is suitable as a source of data. In analyzing the data, the author used SPSS (Statistical Product and Service Solutions) analysis tools version 20 for windows. The results of this study showed that the religious variable has a correlation value of 0.876, social variable has a correlation value of 0.878, economics variable has a correlation value of 0.869 and geographical variable has a correlation value of 0.860. Overall, it can be concluded that the religious, social, economic, and geographical variables have a positive relationship with the Acehnese’s behaviorin choosing Islamic banking products.